Self-Renewal Signalling in Presenescent Tetraploid IMR90 Cells. (6th April 2011) - Huna, Anda; Salmina, Kristine; Jascenko, Elina; Duburs, Gunars; Inashkina, Inna; Erenpreisa, Jekaterina
Abstract : Endopolyploidy and genomic instability are shared features of both stress-induced cellular senescence and malignant growth. Here, we examined these facets in the widely used normal human fibroblast model of senescence, IMR90. At the presenescence stage, a small (2–7%) proportion of cells overcome the 4n-G1 checkpoint, simultaneously inducing self-renewal (NANOG-positivity), the DNA damage response (DDR; γ -H2AX-positive foci), and senescence (p16inka4a- and p21CIP1-positivity) signalling, some cells reach octoploid DNA content and divide. All of these markers initially appear and partially colocalise in the perinucleolar compartment. Further, with development of senescence and accumulation of p16inka4a and p21CIP1, NANOG is downregulated in most cells. The cells increasingly arrest in the 4n-G1 fraction, completely halt divisions and ultimately degenerate. A positive link between DDR, self-renewal, and senescence signalling is initiated in the cells overcoming the tetraploidy barrier, indicating that cellular and molecular context of induced tetraploidy during this period of presenescence is favourable for carcinogenesis.